2013
DOI: 10.1038/nature12071
|View full text |Cite
|
Sign up to set email alerts
|

Slower recovery in space before collapse of connected populations

Abstract: Slower recovery from perturbations near a tipping point and its indirect signatures in fluctuation patterns have been suggested to foreshadow catastrophes in a wide variety of systems1,2. Recent studies of populations in the field and in the laboratory have used time-series data to confirm some of the theoretically predicted early warning indicators, such as an increase in recovery time or in the size and timescale of fluctuations3–6. However, the predictive power of temporal warning signals is limited by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
181
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(182 citation statements)
references
References 33 publications
1
181
0
Order By: Relevance
“…batch culture using synthetic media supplemented with sugar sucrose; on each day the cells were diluted and transferred into fresh media. As demonstrated previously (22,23), yeast populations experience a tipping point (fold bifurcation) leading to sudden collapse as a result of the cooperative breakdown of sucrose outside of the cell. The first driver is the dilution factor used for daily transfer into fresh media (Fig.…”
Section: Significancementioning
confidence: 92%
See 1 more Smart Citation
“…batch culture using synthetic media supplemented with sugar sucrose; on each day the cells were diluted and transferred into fresh media. As demonstrated previously (22,23), yeast populations experience a tipping point (fold bifurcation) leading to sudden collapse as a result of the cooperative breakdown of sucrose outside of the cell. The first driver is the dilution factor used for daily transfer into fresh media (Fig.…”
Section: Significancementioning
confidence: 92%
“…Theoretical and empirical studies have found that signatures of "critical slowing down" in the spatiotemporal dynamics may be used to indicate impending tipping points (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). These indicators are based on the fact that the dynamics around the equilibrium of a system slows down near a tipping point (19,30,31).…”
mentioning
confidence: 99%
“…Moreover, the use of well-designed experiments in highly simplified microbial systems can make even complex problems tractable [34].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, statistics related to variance or autocorrelation could be indicators of declining resilience or approaching thresholds (10,11). Experimental tests of declining resilience in living systems are rare (12)(13)(14)(15)(16)(17), especially in large-scale field settings. In terrestrial ecosystems, such as forests and grasslands, changing resilience has been measured by analyzing the spatial patterns of vegetation maps obtained by satellite remote sensing (18,19).…”
mentioning
confidence: 99%